The Determinants of Profitability In Processed Food Industry In Indonesia - Ren Ren Guo (Universitas Muhammadiyah Jakarta, 2022)
The main purpose of this study is to explore the impact of working capital, sales growth, debt to equity, and operating efficiency ratio on the profitability of processed food industry in Indonesia. The profitability in this study is measured through return on equity (ROE). The research is a quantitative research method by using secondary data for seventeen processed food companies listed in Bursa Efek Indonesia from 2013 until 2019.The research shows:1) working capital has significant positive effect on processed food company’s profitability; 2) Sales growth has significant negative effect on processed food company’s profitability; 3) the debt to equity or leverage does not have any effect on processed food company’s profitability, 4) operating efficiency ratio has significant negative effect on processed food company’s profitability.